Penataan Kawasan Pemukiman Kumuh Kelurahan Tamamaung Kota Makassar - Andas Budy; Fredy (Universitas Muslim Indonesia, 2016)
Slum management actually needs to be carried out not only in slum areas that are part of metropolitan cities or big cities, but also in slums in the smallest part of cities. The handling of slums in large cities and small towns becomes strategic when these areas have a direct influence on parts of the metropolitan city such as the metropolitan city center area, the regional growth center of the metropolis, trade, warehousing, and other offices and industrial areas. In addition to having a direct relationship, it is suspected that slums in the buffer area have difficulty in dealing with slums in the metropolitan city. For this reason, it is necessary to identify the location of slums in the buffer area. Identification of targets from the location of the emphasis slum in the interior of the metropolitan city in the buffer zone, namely Tamamagung Village. The purpose of this study is to analyze the problem of slums and improve the quality of urban settlements which can determine what needs to be considered in designing an environment or even a city to avoid slum areas and then arrange the residential area to be better. The research method used is to use literature and surveys, which produce data then the data will be analyzed and several analysis suggestions will be obtained. The expected result is to be able to design the arrangement of slum areas based on data, analysis and considerations in designing, especially in Tamamaung Village, Makassar City which is the main case study.